Etika dan Tanggung Jawab Sosial Dalam Humas Perspektif Islam - Robbani, Hamdan; Masnawati, Ely (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This introduction explains the important role of public relations as a bridge between organizations and the public, described as a professional profession with ethical responsibilities. This research uses a qualitative approach with a literature review method to explore ethics in public relations from an Islamic perspective, which consists of six fundamental moral principles that public relations practitioners must uphold. Additionally, an investigation into social responsibility in public relations is discussed, referencing the historical and theoretical connections of public relations practices that have existed since the time of the Prophet Muhammad (PBUH). Each phase in public relations management, from research to evaluation, demonstrates the importance of ethics and social responsibility in the effectiveness of communication and the development of positive relationships with the public, which in turn contributes to the achievement of organizational goals.